2014
DOI: 10.1088/0022-3727/47/8/085201
|View full text |Cite
|
Sign up to set email alerts
|

Negative-ion production on carbon materials in hydrogen plasma: influence of the carbon hybridization state and the hydrogen content on Hyield

Abstract: Highly oriented poly crystalline graphite (HOPG), boron-doped diamond (BDD), nanocrystalline diamond (NCD), ultra-nano-crystalline diamond (uNCD), fullerenes C60 and C70 and Diamond Like Carbon (DLC) surfaces are exposed to low pressure hydrogen plasma in a 13.56 MHz plasma reactor. Relative yields of surface produced Hions due to bombardment of positive ions from the plasma are measured by an energy analyzer cum quadrupole mass spectrometer. Irrespective of plasma conditions (0.2 and 2 Pa), HOPG surfaces show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(94 citation statements)
references
References 89 publications
(101 reference statements)
9
85
0
Order By: Relevance
“…This also is mandatory for suitable materials for efficient H − formation in negative hydrogen ion sources. It is scheduled to extend the present investigations on materials for which negative ion surface formation has been reported like highly ordered pyrolytic graphites (HOPG) and different diamond samples [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This also is mandatory for suitable materials for efficient H − formation in negative hydrogen ion sources. It is scheduled to extend the present investigations on materials for which negative ion surface formation has been reported like highly ordered pyrolytic graphites (HOPG) and different diamond samples [14].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations on materials suitable for H − formation at a material surface or close to it are present focusing on various applications and are performed within a wide range of fields and parameters [5][6][7][8][9][10][11][12][13][14]. For example have tantalum and tungsten revealed an enhancing effect on highly vibrationally excited hydrogen molecules H 2 (X,ν) in gas phase experiments [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Carbon materials, in particular non-doped and boron-doped diamond (BDD) have also shown to produce negative hydrogen ions (see e. g. [10,11]). However, in contrast to low work function materials, the formation mechanism at the insulating diamond surface (work function above 4 eV) and thus the actually required conditions for efficient H − production are not fully understood at present.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that carbon materials are interesting candidates to enhance negative ion production in hydrogen plasmas . In a series of papers, negative ion surface production mechanisms on hydrogenated carbon materials have been investigated, pointing out how Raman spectroscopy can be a useful tool for relating surface modification and ion production.…”
Section: Introductionmentioning
confidence: 99%